Unique nanometer-thick layered network - Jung, OS; Kim, YJ; Lee, YA; Yoo, KH (CHEMICAL SOC JAPAN, 2002)
4,6-Bis(2'-pyridylthio)pyrimidine coordinates to three Ag(I) ions in a bridged tridentate fashion to generate the anion exchangeable nanometer-thick layered network.